PENGARUH KOMPRES HANGAT DENGAN BULI – BULI TERHADAP TINGKAT NYERI PUNGGUNG IBU HAMIL TRIMESTER III - Nurulicha, Nurulicha; Perwitasari, Perwitasari; Puspita Sari, Ayu Lestari (JURNAL KESEHATAN INDRA HUSADA, 2024)
Low back pain (LBP) is one of several complaints frequently experienced by pregnant women throughout the world. The hormones relaxin and progesterone will relax the ligaments in the pelvic area and weight gain will change the size of the uterus to become larger, resulting in discomfort in the back area. To prevent the risks of pharmacological therapy, it is important to know complementary therapies that are effective and efficient. The aim of this study was to determine the effect of warm compresses using bladder media on the level of back pain in third trimester pregnant women. This research employed a quasi-experimental method with one group pre-post-test. The total sample of 28 respondents was taken from PMB "F" Klapanunggal Bogor in March 2023. The patient's pain level was measured using the NRS (numeric rating scale) instrument. Data analysis used the paired t-test. The research results showed that the mean or average score before back pain for respondents was 2.68 with a standard deviation value of 0.146, while the average score after back pain in third trimester pregnant women was 1.61 with a standard deviation value of 0.094. Statistical analysis using the paired sample t test obtained a p-value = 0.000 (<0.05), so it can be concluded that there is a significant effect of giving warm compresses on reducing back pain in pregnant women in the third trimester. This research recommends the use of warm compresses as an alternative method for treating back pain experienced during pregnancy.